Heart Rate Variability: A Novel Modality for Diagnosing Neuropathic Pain after Spinal Cord Injury - Karri, Jay; Zhang, Larry; Li, Shengai; Chen, Yen-Ting; Stampas, Argyrios; Li, Sheng (Frontiers in Physiology, 2017)
Background: Heart rate variability (HRV), the physiological variance in the heart’s R-R interval length, can be analyzed to produce various parameters reflective of one’s autonomic balance. HRV analysis may be used to capture those autonomic aberrations associated with chronic neuropathic pain (NP) in spinal cord injury (SCI). This study assesses the capacity of HRV parameters to diagnose NP in an SCI cohort. Methods: An electrocardiogram (ECG) was collected at rest from healthy controls (HC, n=15), patients with SCI only (SCI-NP, n=11), and those with SCI and NP (SCI+NP, n=20). HRV parameters were analyzed using conventional time and frequency analysis. Results: At rest, there were no heart rate differences amongst groups. However, SCI+NP subjects demonstrated lower overall HRV, as determined by the SDNN time domain parameter, compared to either HC (p< 0.01) or SCI-NP (p < 0.05) groups. Moreover, HC and SCI-NP patients were statistically comparable for all HRV time and frequency domain parameters. Additional analyses demonstrated no differences in HRV parameters between T4, above vs. T5, below SCI groups (for all parameters: p > 0.15) or between C8, above vs. T1, below SCI groups (p > 0.30). Conclusions: Patients with SCI and NP exhibit a lower overall HRV, which can be determined by HRV time domain parameter SDNN. HRV analysis is an innovative modality with the capacity for objective quantification of chronic NP in patients with SCI.